ANALYSIS OF THE EFFECT OF RAINFALL ON SEASONAL VARIATION PARTICULATE MATTER 2.5 CONCENTRATION IN MEDAN CITY - Tiara Sutrisno, Rossi
Medan city has a significant growth compared to other cities in North Sumatra, especially seen from the number of motor vehicles and residents that ranked first based on BPS data in 2020. Based on previous studies rainfall can affect air pollution. One of the pollutants that is harmful to health is PM2.5.However, the impact of rainfall on PM2.5 spatially and temporally in Medan City is still not explored. . The purpose of this study is to find out the relationship between rainfall and PM2.5 distribution spatially and temporarily in Medan City in each season during the period December 2014 to November 2022. This study uses monthly rainfall data from GPM and PM2.5 concentration data from MODIS. This study detects outlier data. Furthermore, this study uses temporal plots, scatter plots, and spatial maps to do analysis. The results of this study show that temporally based on the average per season, rainfall generally has an effect on decreasing PM2.5 concentration, but the strength of this effect varies depending on the season. In the MAM, there is a more significant decrease compared to the other seasons at y = -0.15x + 83.61. There should be a more significant decrease in PM2.5 concentrations as rainfall increases. However, even though the rainfall is in a range that is not too different between 150 mm/month and 250 mm/month, the PM2.5 concentration has varying values, some are higher and some are lower. Spatially based on the average per season, shows that in each season the concentration of PM2.5 in the southern part of Medan City tends to be lower than in the northern part. This is related to the higher rainfall that occurs in the southern part of Medan City in each season.